Comparison of gastrointestinal symptoms in colorectal carcinoma patients and community controls with respect to age. Issue 9 (September 1994) - Curless, R; French, J; Williams, G V; James, O F
Abstract : Early diagnosis of colorectal cancer may be delayed by the wide prevalence of gastrointestinal symptoms in the general population. This study assessed, with respect to age, the frequency of gastro-intestinal symptoms in patients with colorectal carcinoma in comparison with community controls and also compared the frequency of such symptoms between 'young' (under 70 years) and 'old' (70 year or over) subjects. Two hundred and seventy three consecutive unselected colorectal cancer patients and 273 age and sex matched community controls were interviewed in a structured manner. Among controls, the 'old' group compared with the 'young' reported abdominal pain (p < 0.05), mucous discharge (p < 0.01), faecal incontinence (p < 0.05), change in flatus production (p < 0.05) significantly more often. There were no significant differences in regularity and frequency of bowel habit by age group. All the symptoms considered were significantly more common in colorectal cancer cases than controls (except abdominal bloating), but the association was less strong in the 'old' group. This study confirms that symptoms attributable to the lower gastrointestinal tract are reported by a clinically important number of community subjects and by a significantly higher proportion of elderly people.